Discharging Mental Health Patients in Aceh: A Preliminary Study - Marty Mawarpury; Arum Sulistyani; Karjuniwati; Hasmila Sari; Rachmalia; Yulia Direzkia; Subhan Rio Pamungkas (ANIMA Indonesian Psychological Journal, 2014)
A high prevalence of mental health patients in Aceh has caused the number of referrals in mental health institutions to rise. An appropriate discharge planning could ensure that patients will be able to continue to treat themselves after they leave the mental health institutions. The objective of this study was to describe the existing discharge planning process of mental health patients in Aceh. Research data was obtained by interviews, observations, and focus group discussions with schizophrenic patients' family members, important figures in the society and in their faith communities, and various officials at Puskesmas (community health centers), RSUD (local hospitals), and RSJ (mental health institutions). Research results show that the process of discharge did not proceed systematically and optimally. Moreover, there is no optimal coordination between mental health institutions and the surrounding communities, resulting in gaps of health services in Aceh. A better and more systematic discharge system are discussed to get the best results. Tingginya jumlah pasien gangguan jiwa menyebabkan rujukan pasien ke RSJ di Aceh meningkat. Suatu perencanaan pelepasan pasien (discharge planning) yang baik dapat menjamin pasien mampu melakukan tindakan perawatan diri sendiri/lanjutan setelah meninggalkan rumah sakit jiwa. Studi ini bertujuan untuk mendapatkan gambaran pelaksanaan pelepasan pasien gangguan jiwa di Aceh selama ini. Data diperoleh dengan metode wawancara, observasi dan FGD pada keluarga pasien skizofrenia, tokoh agama dan masyarakat, petugas kesehatan di Puskesmas, RSUD, dan RSJ. Hasil menunjukkan bahwa pelaksanaan pelepasan pasien tidak berjalan secara sistematis dan optimal. Selain itu koordinasi antara pelayanan kesehatan di RS dan komunitas juga tidak optimal, sehingga menimbulkan kesenjangan pelayanan kesehatan di Aceh. Didiskusikan perlunya pelaksanaan sistem pelepasan pasien yang sistematis dan optimal demi tercapainya hasil yang terbaik.